Systematic Literature Review in Modern Slavery in Operations - Kostopoulou, Sofia (2016)
The phenomenon of modern slavery in operations is, as it is indicated by its term, a contemporary slavery issue which occurs in the context of operations. It entails the situation where workers are forced to work with violent and inhuman methods. A huge number of people around the world suffer from being victims of slavery globally. It is calculated that the number of slaves reaches the 45.8 million worldwide, according to the Global Slavery Index (GSI). This number will continue to be increased if each participant does not take the responsibility and the appropriate measures. The victims of slavery are not only adults, but children as well. That is maybe one of the reasons why academics has recently started to shed light on the topic of modern slavery, or, in other words, on forced labour in operations. Forced labour incorporates various forms, such as, child (forced) labour, human trafficking, and bonded labour – debt bondage. All these different forms have to be studied separately in order to comprehend the phenomenon in depth. Some researchers disagree upon the reasons which enable the perpetuation of the phenomenon and which, finally, give rise to it. Moreover, there are numerous perspectives to solve the problem. In order for all these to be identified, the method of Systematic Literature Review is applied. It is concluded that the solution lies in the collective organisational, institutional, governmental and non-governmental effort.